Estudo da extração mecânica de bixina das sementes de urucum em leito de jorro - Cunha, Fabiano Guimarães e (2008)
The interest and the consumption of natural dyes have been increasing over the last years. The urucum seeds have a dye located in their external layer called bixin. The spouted bed, since it is an inexpensive equipment and because of its simple operation, can be an excellent alternative for mechanical extraction of the bixin from the surface of the urucum seeds, on small and average country properties. However, despite having some interesting fluidodinamics characteristics for the related application, such as an intense movement of particles and an effective gas-solid contact, the spouted bed presents some restrictions that have limited its application. This work had as objective to study the effect of the variables: use of the draft, the load of the urucum seeds and the air velocity on the process of the mechanical extraction of the bixin in a spouted bed. The computational fluidodinamics technique (CFD) was used to describe numerically the behavior both of the urucum seeds and the air inside the spouted bed. By means of the results obtained it was possible to achieve the operational conditions that maximize the efficiency of removal and allow the attainment of a product with the appropriate quality. From the experimental planning, carried through in order to study the effect of the load of the seeds, the air flow and the presence of the draft in the mechanical extraction of the bixin from urucum seeds, it was possible to get to the conclusion that the presence of the "draft" was the variable that had the highest effect in all the studied answer variables (mass of extracted powder, productivity and bixin concentration). Since the presence of the draft showed to be the variable that governs the attrition kinetics, the effect of the distance from the draft base to the spouted bed base (ht) was studied, in view of the maximization of the dyeing production. The experimental results showed that the distance from the draft base to the spouted bed base (ht) that most favors the mechanical extraction of the bixin in spouted bed was the one of 4cm. The results of the simulation through CFD also helped in the understanding of the best performance for the configuration of the spouted bed using a draft, placed at ht = 4 cm. Through the simulations, it was also possible to get values of velocity for the condition of minimum spouting, close to the experimental values, with relative errors of about 4%.